MATHEMATICAL MODEL OF AGING IN COVID 19 - Jovanikic, Olivera (Journal of Medical Biochemistry, 2022)
Background. Examination of the intima-media thickness of carotid arteries in COVID-19 infection. Methods. In 50 patients the thickness of the intimomedial complex (IMT) in the common carotid arteries was measured. The values were compared with the control group in 2006-9. The condition of the lungs was assessed by sonography - mild (0-14) or medium-severe (15-28) covid. IMT thickening risk factors and the value of fibrinogen, IL-6 and CRP were recorded. Two IMT prediction models were formed. The socio-epidemiological model predicts the development of IMT based on epidemiological factors. The second model, apart from these factors, also includes the values of the mentioned biomarkers. Results. It score 20±6,; IMT right 1.024±0.272; left 0.999±0.224. Control: IMT 0.78±0.27; left 0.79±0.27. The group/control difference is highly significant. Epidemiological model: logit (IMT)= 4.463+(2.021+value for GEN)+ (0. 055x AGE value)+(-3.419x RFvalue)+(-4.447x SM value)+(5.115x HTA value)+ (3.56x DMvalue)+(22.389x LIP value)+(24.206x CVD value)+( 1.449x other value)+(-0.138x IT score value)+(0.19xBMI value). Epidemiological-inflammatory model: logit(IMT)=5.204+(2.545x GEN value)+(0.076x AGE value)+(-6.132x RF value)+(-7.583x SM value)+(8.744x HTA value) + (6.838x DM value)+(25.446x LIP value )+(28.825x CVD value)+(2.487x other value)+(-0.218xIt score value)+( 0.649x BMI value) +(-0.194x fibrinogen value)+(0.894x IL-6 value)+( 0.659x CRP value). Values ​​for both models Exp(B)=4.882; P of sample=0.83; logit=-0.19; OR=23.84; model accuracy for first model 87% and for second 88%; Omnibus test of the first model χ2=34.324;p=0.000; reliability coefficient –2LogLH=56, 854 Omnibus test of the second model χ2=39.774;p=0.000; -2LogLH=51,403. Conclusion. Aging of blood vessels in COVID-19 can be predicted. Abbreviations: IMT- thickening of the intima-media complex; GEN - sex; AGE-years; RF - number of risk factors; DM-diabetes; SM-smoking; HTA-hypertension; LIP-lipidemia; CVD- cardiovascular diseases; second - other diseases or condition important for IMT; BMI - body mass index.